Predictive value of platelet to lymphocyte ratio and mean platelet volume in atrial fibrillation after isolated coronary artery bypass graft operation (Annals of Medical Research, 2021)
None
Keywords: Atrial fibrillation; coronary artery bypass graft operation; inflammation; mean platelet volume; platelet to lymphocyte ratio